A Brief Review of Formaldehyde Removal through Activated Carbon Adsorption - Yu-Jin Kang; Hyung-Kun Jo; Min-Hyeok Jang; Xiaoliang Ma; Yukwon Jeon; Kyeongseok Oh; Joo-Il Park (Applied Sciences, 2022)
Formaldehyde is a highly toxic indoor pollutant that can adversely impact human health. Various technologies have been intensively evaluated to remove formaldehyde from an indoor atmospheres. Activated carbon (AC) has been used to adsorb formaldehyde from the indoor atmosphere, which has been commercially viable owing to its low operational costs. AC has a high adsorption affinity due to its high surface area. In addition, applications of AC may be diversified by the surface modification. Among the different surface modifications for AC, amination treatments of AC have been reported and evaluated. Specifically, the amine functional groups of the amine-treated AC have been found to play an important role in the adsorption of formaldehyde. Surface modifications of AC by impregnating and/or grafting the amine functional groups onto the AC surface have been reported in the literature. The impregnation of the amine-containing species on AC is mainly achieved by physical interaction or H-bond of the amines to the AC surface. Meanwhile, the grafting of the amine functional groups is mainly conducted through chemical reactions occurring between the amines and the AC surface. Herein, the carboxyl group, as a representative functional group for grafting on the surface of AC, plays a key role in the amination reactions. A qualitative comparison of amination chemicals for the surface modification of AC has also been discussed. Thermodynamics and kinetics for adsorption of formaldehyde on AC are firstly reviewed in this paper, and then the major factors affecting the adsorptive removal of formaldehyde over AC are highlighted and discussed in terms of humidity and temperature. In addition, new strategies for amination, as well as the physical modification option for AC application, are proposed and discussed in terms of safety and processability.